Multi-element doped hafnium oxide thermal / environmental barrier coating material capable of resisting molten sand dust corrosion as well as preparation method and application of multi-element doped hafnium oxide thermal / environmental barrier coating material
By doping Y2O3, Gd2O3 and Yb2O3 into HfO2 in the thermal/environmental barrier coating material, the multi-component rare earth hafnium oxide structure is solved, and the existing materials cannot be insulated at the same time and resist extreme environments is achieved, achieving higher oxidation and corrosion resistance.
Patent Information
- Application Number
- CN202411951593.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-25
AI Technical Summary
Existing thermal/environmental barrier coating materials are unable to meet the problems of thermal insulation and resistance to extreme environmental capabilities while facing complex thermophysical and chemical and stress environments.
Using a multivariate doped hafnium oxide thermal/environmental barrier coating material, a multivariate rare earth hafnium oxide structure with excellent comprehensive performance is formed by doping Y2O3, Gd2O3 and Yb2O3 dopants into the HfO2 matrix. This material is prepared by a high-temperature solid phase reaction method to form a coating with high melting point, low thermal conductivity and excellent high-temperature phase stability.
This material can not only prevent further penetration of CMAS, but also be used for a long time under extreme temperature conditions, significantly improving the anti-oxidation and corrosion resistance and effectively protecting the matrix material.
Smart Images

Figure CN119684039A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of corrosion protection, and in particular relates to a multinary doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand dust corrosion, and a preparation method and application thereof. Background Art
[0002] As aircraft engines develop towards high thrust-to-weight ratio and high fuel efficiency, the temperature at the engine turbine inlet continues to increase and is expected to reach 1400°C or above, which exceeds the temperature limit of high-temperature alloys. SiC-CMC (silicon carbide-ceramic matrix composite) has the advantages of low density, high temperature resistance, oxidation resistance and creep resistance, and is expected to become an ideal material to replace high-temperature alloys. However, in actual service environments, water vapor-oxygen and calcium magnesium aluminum silicate (Cao-MgO-Al 2 O 3 -SiO 2 Compounds, referred to as CMAS) corrosive media can cause corrosion failure of SiC-CMC hot end components.
[0003] In order to ensure the service reliability of hot end components, thermal / environmental barrier coatings (T / EBCs) were designed. The coating system includes a silicon bonding layer, a rare earth silicate intermediate layer, and a surface layer (TBC) represented by rare earth zirconates and hafnates. The silicon bonding layer can relieve stress mismatch and generate SiO 2 , preventing oxygen diffusion; rare earth silicates can prevent high-temperature water vapor from corroding SiC-CMC; TBC can reduce the impact of CMAS while providing thermal insulation performance. Since TBC is the outermost layer of T / EBCs, it will be directly exposed to high temperature and corrosive environments, so it has higher requirements for tolerance to high-temperature thermal corrosion. However, the TBC materials of existing T / EBCs cannot meet the problems of thermal insulation and resistance to extreme environments at the same time when facing complex thermal physical chemistry and stress environments. Summary of the invention
[0004] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a multi-doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand dust corrosion and a preparation method and application thereof, so as to solve the technical problem that the TBC material of existing T / EBCs cannot have both corrosion resistance and thermal protection capabilities.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions: In a first aspect of the present invention, a multi-element doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand dust corrosion is disclosed, which comprises, by mole percentage, 3% to 14% of Y 2 O 3, 1%~3% Gd 2 O 3 and 1%~3% Yb 2 O 3 , the remainder is HfO 2 .
[0006] Preferably, Y 2 O 3 , Gd 2 O 3 , Yb 2 O 3 and HfO 2 The particle size is 20~80 nm.
[0007] The second aspect of the present invention discloses a method for preparing the above-mentioned multi-doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand dust corrosion, wherein Y 2 O 3 , Yb 2 O 3 , Gd 2 O 3 and HfO 2 The powders are mixed, ball-milled, treated by a high-temperature solid phase reaction method, cooled, crushed, and sieved to obtain a multi-element doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand and dust corrosion.
[0008] Preferably, during ball milling, anhydrous ethanol or deionized water is used as the dispersion medium.
[0009] Preferably, the ball milling time is 10 to 24 h.
[0010] Preferably, the reaction conditions of the high temperature solid phase reaction method are to keep the temperature at 1200-1450° C. for 1-5 h.
[0011] Preferably, the reaction atmosphere of the high temperature solid phase reaction is air or nitrogen.
[0012] The third aspect of the present invention discloses the application of the above-mentioned multi-element doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand and dust corrosion in the fields of aerospace and energy.
[0013] The fourth aspect of the present invention discloses the application of the above-mentioned multi-component doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand and dust corrosion in an engine fuel gas environment.
[0014] The fifth aspect of the present invention discloses a multinary doped hafnium oxide thermal / environmental barrier coating resistant to molten sand and dust corrosion, wherein the surface layer is formed by spraying the multinary doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand and dust corrosion.
[0015] A sixth aspect of the present invention discloses an aircraft engine, wherein the surface of the hot end component of the aircraft engine is sprayed with the above-mentioned multi-element doped hafnium oxide thermal / environmental barrier coating resistant to molten sand and dust corrosion.
[0016] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a multi-element doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand and dust corrosion, wherein the main rare earth oxide dopant Y 2 O 3 , double auxiliary rare earth oxide dopant Gd 2 O 3 and Yb 2 O 3 These rare earths are mixed into HfO as the matrix 2 In the process, a multi-component rare earth hafnium oxide structure with excellent comprehensive performance can be formed, which can not only prevent further penetration of CMAS, but also help the long-term use of the material under extreme temperature conditions. The material is sprayed onto the surface of the substrate to form a coating structure with HfO 2 As the matrix, rare earth oxide (Y 2 O 3 , Yb 2 O 3 , Gd 2 O 3 ) is a multi-component solid solution, HfO 2 It is stable at high temperatures and has a high melting point and corrosion resistance. The addition of rare earth oxides will cause CMAS to form a dense oxide film on the surface of the material after corrosion, improving the anti-oxidation and anti-corrosion properties. 2 O 3 As the main rare earth dopant, it can effectively improve the mechanical strength and high temperature stability of the material; Yb 2 O 3 and Gd 2 O 3 As a dual auxiliary rare earth dopant, it further enhances the material's oxidation resistance and high temperature resistance. Experiments have shown that the coating formed by this material presents a defective fluorite structure (space group Fm3m, No. 227) with disordered oxygen vacancies, and the multi-component solid solution effect stabilizes the dual auxiliary rare earth elements Gd and Yb into the defective fluorite structure dominated by the main rare earth element Y, making the multi-component rare earth hafnium oxide defective fluorite structure performance comprehensively optimized.
[0017] Compared with rare earth zirconate, a commonly used surface material of thermal barrier coatings, the coating formed by the multi-doped hafnium oxide thermal / environmental barrier coating material of this method has the characteristics of higher melting point, lower thermal conductivity, better high-temperature phase stability and a thermal expansion coefficient that is more compatible with SiC-CMC composite materials. It shows greater advantages when used as the outermost TBC. Through the reasonable regulation of the doping ratio, the synergistic effect of rare earth oxides and HfO 2 The high temperature stability of the substrate enables the coating formed by this material to effectively resist sand and dust corrosion in harsh working environments, thereby ensuring the performance and reliability of key components such as aircraft engine components and turbine blades.
[0018] The method for preparing the above-mentioned multi-doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand and dust corrosion provided by the present invention adopts a high-temperature solid-phase reaction method to synthesize the multi-doped hafnium oxide thermal / environmental barrier coating material. The prepared material has small particles, fluffy powder, is not easy to agglomerate, has good filling properties, and has the advantages of simple operation, large production volume and fewer processes.
[0019] The invention provides a multi-doped hafnium oxide thermal / environmental barrier coating resistant to molten sand and dust corrosion. The multi-doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand and dust corrosion is used as a surface layer, has a high melting point, low thermal conductivity, excellent high-temperature phase stability and a thermal expansion coefficient that is more compatible with the SiC-CMC composite material. The rare earth oxide doping can be carried out after CMAS corrosion on the HfO 2 A solid oxide film is formed on the surface of the substrate to protect the substrate from corrosion by molten sand and dust. At the same time, the incorporation of rare earth elements can also change the microstructure of the material, enhance its corrosion resistance, and effectively protect the substrate material. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 3%Y of Example 1 of the present invention 2 O 3 -1%Gd 2 O 3 -1%Yb 2 O 3 -95%HfO 2 X-ray diffraction pattern of the prepared sample; Figure 2 7%Y of Example 2 of the present invention 2 O 3 -1.5%Gd 2 O 3 -1.5%Yb 2 O 3 -90%HfO 2 X-ray diffraction pattern of the prepared sample; Figure 3 14%Y of Example 3 of the present invention2 O 3 -3%Gd 2 O 3 -3%Yb 2 O 3 -80%HfO 2 X-ray diffraction pattern of the prepared sample; Figure 4 3%Y of Example 1 of the present invention 2 O 3 -1%Gd 2 O 3 -1%Yb 2 O 3 -95%HfO 2 Backscattering morphology of the sample after CMAS corrosion at 1300℃ for 20 h; A is 10 kx times and B is 20 kx times; Figure 5 7%Y of Example 2 of the present invention 2 O 3 -1.5%Gd 2 O 3 -1.5%Yb 2 O 3 -90%HfO 2 Backscattering morphology of the sample after CMAS corrosion at 1300℃ for 20 h; A is 10 kx times and B is 20 kx times; Figure 6 14%Y of Example 3 of the present invention 2 O 3 -3%Gd 2 O 3 -3%Yb 2 O 3 -80%HfO 2 Backscattering morphology of the sample after CMAS corrosion at 1300℃ for 20 h; A is 10 kx times and B is 20 kx times; Figure 7 3%Y of Example 1 of the present invention 2 O 3 -1%Gd 2 O 3 -1%Yb 2 O 3 -95%HfO 2 Backscattering morphology of the sample after CMAS corrosion at 1400℃ for 20 h; A is 10 kx times and B is 20 kx times; Figure 8 7%Y of Example 2 of the present invention 2 O 3 -1.5%Gd2 O 3 -1.5%Yb 2 O 3 -90%HfO 2 Backscattering morphology of the sample after CMAS corrosion at 1400℃ for 20 h; A is 10 kx times and B is 20 kx times; Fig. 9 14%Y of Example 3 of the present invention 2 O 3 -3%Gd 2 O 3 -3%Yb 2 O 3 -80%HfO 2 Backscattered morphology of the prepared sample after CMAS corrosion at 1400℃ for 20 h; A is 10 kx times and B is 20 kx times. DETAILED DESCRIPTION
[0021] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0022] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0023] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0024] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0025] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0026] The present invention provides a multi-element doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand and dust corrosion, the chemical formula of which is xY 2 O 3 -yGd 2 O 3 -yYb 2 O 3 -(1-x-2y)HfO 2 , among which, 3%≤x≤14%, 1%≤y≤3%, 5%≤x+2y≤20%.
[0027] The present invention provides a method for preparing the above-mentioned multi-doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand dust corrosion, comprising the following steps: 1. Formulation Multi-doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand dust corrosion, including 3% to 14% Y 2 O 3 , 1%~3% Gd 2 O 3 and 1%~3% Yb 2 O 3 , the remainder is HfO 2 .
[0028] 2. Preparation According to the formula of step 1, weigh the main rare earth dopant Y with a size of 20~80 nm and a powder purity of ≥99.9% 2 O 3 , double auxiliary rare earth dopant Yb 2 O 3 , Gd 2 O 3 and HfO 2 powder to form a mixed raw material, and then ball milling and mixing for 10 to 24 hours to obtain a uniform mixed powder; then the mixed powder is dried, treated by a high-temperature solid phase reaction method, cooled, crushed, dried and sieved to obtain a multi-element doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand dust corrosion; Among them, the ball milling mixing process uses anhydrous ethanol or deionized water as the dispersion medium, and an appropriate amount of dispersant is added to improve the mixing uniformity, thereby improving the performance of the final material; the reaction conditions of the high-temperature solid-phase reaction method are to keep warm at 1200~1450℃ for 1~5 h, and the reaction atmosphere is air or nitrogen to ensure the phase stability of the material.
[0029] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0030] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples, unless otherwise specified, are conventional commercial products, and their specifications are conventional specifications in the art.
[0031] 1. Preparation of multi-doped hafnium oxide thermal / environmental barrier coating materials resistant to molten sand and dust corrosion Example 1 Multi-doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand dust corrosion (3%Y 2 O 3 -1%Gd 2 O 3 -1%Yb 2 O 3 -95%HfO 2 ) is prepared as follows: 1. Calculate the required oxide Y according to the doping amount 2 O 3 , Gd 2 O, Yb 2 O 3 and HfO 2 The masses are 0.48 g, 0.24 g, 0.27 g and 14.01 g (Y 2 O 3 , Gd 2 O, Yb 2 O 3 and HfO 2 The molar ratio is 3:1:1:95), accurately weigh the corresponding nano-grade raw materials with a powder purity of ≥99.9%; 2. Weigh the Y 2 O 3 , Gd 2 O, Yb 2 O 3 and HfO 2 The mixed powder was placed in a zirconia ball mill, and ball milled in a planetary ball mill for 10 h using anhydrous ethanol as a medium to obtain a uniform mixed oxide slurry; 3. Remove anhydrous ethanol from the slurry obtained in step 2) in a vacuum drying oven at 80°C to obtain a dry mixed powder; 4. The mixed powder obtained in step 3) is placed in an alumina crucible, and the temperature is raised to 1000°C at 10°C / min in a box furnace, and then raised to 1200°C at 5°C / min, and kept at this temperature for 5 h, and then lowered to 1000°C at 5°C / min, and then cooled in the furnace; 5. The powder cooled in step 4) was ball-milled again for 24 h, dried and sieved to obtain 3% Y 2 O 3 -1%Gd 2 O 3 -1%Yb 2 O 3 -95%HfO 2 powder.
[0032] Example 2 Multi-doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand dust corrosion (7%Y 2 O 3 -1.5%Gd 2 O 3 -1.5%Yb 2 O 3 -90%HfO 2 ) is prepared as follows: 1. Calculate the required oxide Y according to the doping amount 2 O 3 , Gd 2 O, Yb 2 O 3 and HfO 2 The masses are 1.11 g, 0.39 g, 0.42 g and 13.11 g (Y 2 O 3 , Gd 2 O, Yb 2 O 3 and HfO 2 The molar ratio is 7:1.5:1.5:90), accurately weigh the corresponding nano-grade raw materials with a powder purity of ≥99.9%; 2. Weigh the Y 2 O 3 , Gd 2 O, Yb 2 O 3 and HfO 2 The mixed powder was placed in a zirconia ball milling jar and milled in a planetary ball mill for 18 h using anhydrous ethanol as a medium to obtain a uniform mixed oxide slurry; 3. Remove anhydrous ethanol from the slurry obtained in step 2) in a vacuum drying oven at 80°C to obtain a dry mixed powder; 4. The mixed powder obtained in step 3) is placed in an alumina crucible and heated to 1000°C at 10°C / min in a box furnace, then heated to 1300°C at 5°C / min, kept at this temperature for 3 h, then cooled to 1000°C at 5°C / min, and then cooled in the furnace; 5. The powder cooled in step 4) was ball-milled again for 24 h, dried and sieved to obtain 7% Y 2 O 3 -1.5%Gd 2 O 3 -1.5%Yb 2 O 3 -90%HfO 2 powder.
[0033] Example 3 Multi-doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand dust corrosion (14%Y 2 O 3 -3%Gd 2 O 3 -3%Yb 2 O 3 -80%HfO 2 ) is prepared as follows: 1. Calculate the required oxide Y according to the doping amount 2 O 3 , Gd 2 O, Yb 2 O 3 and HfO 2 The masses are 2.13 g, 0.72 g, 0.81 g and 11.34 g (Y 2 O 3 , Gd 2 O, Yb 2 O 3 and HfO 2 The molar ratio is 14:3:3:80), accurately weigh the corresponding nano-grade raw materials with a powder purity of ≥99.9%; 2. Weigh the Y 2 O 3 , Gd 2 O, Yb 2 O 3 and HfO 2 The mixed powder was placed in a zirconia ball milling jar and milled in a planetary ball mill for 24 h using deionized water as the medium to obtain a uniform mixed oxide slurry; 3. Remove anhydrous ethanol from the slurry obtained in step 2) in a vacuum drying oven at 80°C to obtain a dry mixed powder; 4. The mixed powder obtained in step 3) is placed in an alumina crucible, and the temperature is raised to 1000°C at 10°C / min in a box furnace, and then raised to 1450°C at 5°C / min, and kept at this temperature for 1 h, and then lowered to 1000°C at 5°C / min, and then cooled in the furnace; 5. The powder cooled in step 4) was ball-milled again for 24 h, dried and sieved to obtain 14% Y 2 O 3 -3%Gd 2 O 3 -3%Yb 2 O 3 -80%HfO 2 powder.
[0034] 2. Performance testing of multi-doped hafnium oxide thermal / environmental barrier coating materials resistant to molten sand and dust corrosion The 3% Y prepared in Example 1 2 O 3 -1%Gd 2 O 3 -1%Yb 2 O 3 -95%HfO 2 The powder was placed in a mold and cold pressed to obtain a sample of appropriate size. The sample was then placed in an alumina crucible and heated to 1000°C at 10°C / min in a box furnace, then heated to 1500°C at 5°C / min, kept at that temperature for 30 h, then cooled to 1000°C at 5°C / min, and then cooled in the furnace to obtain a dense sample 1 to be tested.
[0035] The 7% Y prepared in Example 2 2 O 3 -1.5%Gd 2 O 3 -1.5%Yb 2 O 3 -90%HfO 2 The powder was placed in a mold and cold pressed to obtain a sample of appropriate size. The sample was then placed in an alumina crucible and heated to 1000°C at 10°C / min in a box furnace, then heated to 1600°C at 5°C / min, kept at that temperature for 20 h, then cooled to 1000°C at 5°C / min, and then cooled in the furnace to obtain a dense sample 2 to be tested.
[0036] The 14% Y prepared in Example 3 2 O 3 -3%Gd 2 O 3 -3%Yb 2 O 3 -80%HfO 2The powder was placed in a mold and cold pressed to obtain a sample of appropriate size. The sample was then placed in an alumina crucible and heated to 1000°C at 10°C / min in a box furnace, then heated to 1700°C at 5°C / min, kept at that temperature for 15 h, then cooled to 1000°C at 5°C / min, and then cooled in the furnace to obtain a dense sample 3 to be tested.
[0037] X-ray diffraction tests were performed on samples 1, 2 and 3 respectively. The test results are as follows: Figure 1 , Figure 2 and Figure 3 As shown, it can be seen that a defective fluorite structure (space group Fm3m, No. 227) with disordered arrangement of oxygen vacancies is obviously formed in the samples, indicating that the multi-doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand and dust corrosion still maintains the defective fluorite structure after the high-temperature solid-phase reaction and has excellent high-temperature phase structure stability.
[0038] Samples 1, 2 and 3 were placed in 1300℃ CMAS corrosion for 20 h and examined using a scanning electron microscope (SEM). The backscattered morphology is shown in Figure 2. Figure 4 , Figure 5 and Figure 6 As shown, it can be seen that the sample has a dense structure, low porosity, and a very small CMAS corrosion thickness, indicating that the sample has obvious resistance to CMAS corrosion.
[0039] Samples 1, 2 and 3 were placed in 1400℃ CMAS corrosion for 20 h and examined using a scanning electron microscope (SEM). The backscattered morphology is shown in Figure 2. Figure 7 , Figure 8 and Fig. 9 As shown, it can be seen that as the corrosion temperature increases to 1400℃, the thickness of the generated corrosion products increases compared with 1300℃ CMAS corrosion for 20 h, but still maintains a low thickness, indicating that the sample still has obvious anti-CMAS corrosion performance at 1400℃.
[0040] 3. Preparation of multi-doped hafnium oxide thermal / environmental barrier coatings resistant to molten sand and dust corrosion A conventional spraying method is used to sequentially prepare a silicon bonding layer and a rare earth silicate intermediate layer on the surface of a base material. Then, a spraying process such as atmospheric plasma spraying is used to spray the multi-doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand and dust corrosion prepared by the above method onto the surface of the rare earth silicate intermediate layer to form a surface layer, thereby obtaining a thermal / environmental barrier coating on the surface of the base material.
[0041] It should be noted that the spraying method of the multi-doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand and dust corrosion includes but is not limited to atmospheric plasma spraying, and can also be physical vapor deposition (such as EB-PVD).
[0042] It should be noted that in order to improve the fluidity of the powder, before spraying, the spray drying method can be used to obtain Y with a particle size of 30~70 μm. 2 O 3 , Gd 2 O 3 , Yb 2 O 3 and HfO 2 Mixed spherical powder.
[0043] It should be noted that, before spraying, the silicon bonding layer, the rare earth silicate intermediate layer and the surface layer can be subjected to appropriate heat treatment according to actual conditions to improve the bonding strength and overall performance between the coatings.
[0044] It should be noted that the substrate is a component that is exposed to a high-temperature working environment for a long time and is susceptible to oxidation and corrosion, such as an aircraft engine and a hot end component of a ground gas turbine.
[0045] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A multi-element doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand and dust corrosion, characterized in that: In terms of molar percentage, it includes 3%~14% Y2O3, 1%~3% Gd2O3 and 1%~3% Yb2O3, and the balance is HfO2.
2. The multi-element doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand and dust corrosion according to claim 1, characterized in that: The particle sizes of Y2O3, Gd2O3, Yb2O3 and HfO2 are 20~80 nm.
3. The method for preparing a multi-element doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand dust corrosion according to claim 1 or 2, characterized in that: Y2O3, Yb2O3, Gd2O3 and HfO2 powders are weighed respectively, mixed, ball-milled, treated by high-temperature solid-phase reaction method, cooled, crushed and sieved to obtain a multi-element doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand dust corrosion.
4. The method for preparing a multi-element doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand dust corrosion according to claim 3, characterized in that: During ball milling, anhydrous ethanol or deionized water is used as the dispersion medium.
5. The method for preparing a multi-element doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand dust corrosion according to claim 3, characterized in that: The reaction conditions of the high-temperature solid-phase reaction method are to keep the temperature at 1200~1450℃ for 1~5 h.
6. The method for preparing a multi-element doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand dust corrosion according to claim 3, characterized in that: The reaction atmosphere for high temperature solid phase reaction is air or nitrogen.
7. Application of the multinary doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand and dust corrosion according to claim 1 or 2 or the multinary doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand and dust corrosion obtained by the preparation method according to any one of claims 3 to 6 in the fields of aerospace and energy.
8. Use of the multinary doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand and dust corrosion according to claim 1 or 2 or the multinary doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand and dust corrosion obtained by the preparation method according to any one of claims 3 to 6 in an engine gas environment.
9. A multi-element doped hafnium oxide thermal / environmental barrier coating resistant to molten sand and dust corrosion, characterized in that: The surface layer is formed by spraying the multi-doped hafnium oxide thermal / environmental barrier coating material resistant to molten sand and dust corrosion as claimed in claim 1 or 2.
10. An aircraft engine, characterized in that: The surface of the hot end component of the aircraft engine is sprayed with the multinary doped hafnium oxide thermal / environmental barrier coating resistant to molten sand and dust corrosion as claimed in claim 9.
Citation Information
Patent Citations
Method for generating A2B2O7 type thermal barrier coating material by laser-induced high-temperature solid-phase reaction
CN109851377A
Preparation method of ceramic material and preparation method of thermal barrier coating
CN110304919A
Nano-structure rare earth hafnate ceramic powder feed for thermal spraying as well as preparation method and application of nano-structure rare earth hafnate ceramic powder feed
CN116023136A
All-oxide thermal / environmental barrier coating for ceramic-based composite material and preparation method of all-oxide thermal / environmental barrier coating
CN116253584A
Environmental barrier coating material for SiC / SiC composite material and preparation method thereof
CN117945752A